Sequential chimeric fibula‐gracilis flap to salvage a complex orbitomaxillary defect: A case report. Issue 3 (28th January 2023) - De Cicco, Davide; Bottini, Gian Battista; Gaggl, Alexander
Abstract: Extended maxillectomies with orbital exenteration and facial soft tissue resection need careful planning to achieve satisfactory functional and esthetic outcomes. Only a few solutions provide enough hard and soft tissue on a single pedicle, and only some reconstructive goals might be achievable with a single flap. This paper describes an original inset of the gracilis muscle free flap, used in a vessels depleted patient to salvage a partially failed multi‐flap reconstruction after an extensive maxillectomy. A 55‐years old man underwent a surgical intervention for a fibrosarcoma of the right maxilla. Due to the disease extension, the resection included right maxilla and palate, the overlying facial soft tissues (including the paranasal, cheek, and infraorbital regions), and the entire orbital content (orbital exenteration). A double flap reconstruction—a free fibula flap and a deep circumflex iliac artery flap—was carried out primarily. However, an intraoperative complication caused a partial flap loss, resulting in a complex tridimensional defect of the orbit and the oral cavity. Therefore, a 18 cm long gracilis muscle free flap was used to fill the defect and save the remaining bony reconstruction. The muscle was inset behind the transplanted bone to seal both the orbit and the oral cavity. No complications occurred after the salvage surgery, with a stable result at the 6‐months follow‐up. The designed gracilis muscle free flap proved a reliable option for this salvage surgery. However, it could be helpful also in the primary reconstruction of extended maxillectomies in combination with another composite free flap.